Recent Advances in Layered MX2-Based Materials (M = Mo, W and X = S, Se, Te) for Emerging Optoelectronic and Photo(electro)catalytic Applications - Pinto, Felipe M.; de Conti, Mary C. M. D.; Pereira, Wyllamanney S.; Sczancoski, Júlio C.; Medina, Marina; Corradini, Patricia G.; de Brito, Juliana F. [UNESP]; Nogueira, André E.; Góes, Márcio S.; Ferreira, Odair P.; Mascaro, Lucia H.; Wypych, Fernando; et al. (MDPI, 2024)
Transition metal dichalcogenides (TMDCs), represented by MX2 (where M = Mo, W and X = S, Se, and Te), and more recently, their moiré superlattices (i.e., formed by superimposing layers of TMDCs with different rotation angles) have attracted considerable interest due to their excellent physical properties and unique nanoscale functionalities. Compared to graphene, the literature indicates that TMDCs offer a competitive advantage in optoelectronic technologies, primarily owing to their compositionally controlled non-zero bandgap. These two-dimensional (2D) nanostructured single or multiple layers exhibit remarkable properties that differ from their bulk counterparts. Moreover, stacking different TMDC monolayers also forms heterostructures and introduces unique quantum effects and extraordinary electronic properties, which is particularly promising for next-generation optoelectronic devices and photo(electro)catalytic applications. Therefore, in this review, we also highlight the new possibilities in the formation of 2D/2D heterostructures of MX2-based materials with moiré patterns and discuss the main critical challenges related to the synthesis and large-scale applications of layered MX2 and MX2-based composites to spur significant advances in emerging optoelectronic and photo(electro)catalytic applications.
Keywords: 2D materials; 2D/2D heterostructures; MX2; transition metals dichalcogenides